Which Dilemmas of Policy Making Under Thatcher and Reagan Can Be Identified in the Transition Economies of 1990s? - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
This paper focuses at the dilemmas that Thatcher and Reagan governments faced. The difficult choices they were faced are analyzed and compared to the ones that policymakers in early 90s in transition countries made.
Keywords: A1; 330; Thatcher; Reagan